Factors affecting the adoption of Voice over Internet Protocol (VoIP) and other converged IP services in South Africa - P. K.J. Tobin; M. Bidoli (South African Journal of Business Management, 2006)
The authors embarked on this study to investigate factors likely to impact on the adoption of VoIP and other converged Internet protocol (IP) services in the SA market. The intention of this study was to lay the groundwork for a comprehensive understanding of the forces shaping the market, in order to help industry participants and new entrants position themselves correctly. This is achieved by evaluating technology adoption and diffusion models, in particular Moore's chasm model, which highlights the reasons why so many new technologies fail to break into the mainstream. Empirical research of business customers and potential customers shows that the two key factors hindering the adoption of these technologies in SA are high bandwidth costs/high costs of services and quality of service Issues. The research also shows that the trend towards IP is well established in SA, with many companies having already invested in, or planning to invest in, VoIP and converged IP services.
Keywords: 650